Histological findings of testicular biopsy in North Indian population - Mahajan, Arpita; Kakar, Smita; Kaul, J. M.; Mishra, Sabita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is defined as the inability to achieve pregnancy after one year of unprotected intercourse. To interpret these testicular causes, biopsy of testis and its classification becomes an important tool for diagnoses. Biopsy is mostly done in severe oligozoospermic or azoospermic patients. Biopsies are also important in recent times due to introduction of Assisted Reproductive Techniques (ART) because they determine the level of spermatogenesis. In the present study the testicular biopsy has been classified into seven categories. One of the classification is that of the highly homogenous mass, which is an addition to the studies done previously. The increase in connective tissue has been demonstrated by Masson’s trichrome stain not cited in the literature. This study will help relook into the way of categorising the testicular biopsy which will benefit those seeking treatment of male infertility. Methods: The study was carried out on 30 infertile patients who were either azoospermic (nil to <2 x106 sperms/ml) or severe oligozoospermic (<5 x106 sperms/ml). Testicular biopsy of these patients was taken after obtaining ethical clearance and written consent of the patients. The biopsy was processed, stained and assessed using haematoxylin and eosin and Masson’s trichrome. They were classified into different histological types. They were also categorised by modified Johnsen scoring. Results: The biopsies were classified histologically into obstructive azoospermia in 4 cases (13.33%). Hypospermatogenesis in 5 cases (16.66%), maturation arrest in 3 cases (10%), sertoli cell only syndrome in 3 cases (10%), seminiferous tubule hyalinization in 7 cases (23.33%), mixed patterns in 6 cases (20%) and highly cellular homogenous tissue in 2 cases (6.66%). The last condition has not been classified in the literature cited. Conclusions: By the present study we can determine the level of spermatogenesis and by studying the nature of different germ cells we can use it for ART. Consideration of the biopsy being taken from a particular part of the testis must be kept in mind, and there might be the possibility of spermatogenesis occurring in some other quadrant. The patient needs to be explained this.